Efektivitas Penggunaan Platform E-Learning Berbasis Moodle untuk Meningkatkan Motivasi Belajar Siswa - Khoirujzaman, Haykal Kholid; Nasrulloh, Sofhian Fazrin (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The rapid development of information and communication technology demands the integration of digital platforms in education to enhance student learning motivation, particularly in vocational high schools. This study aims to measure the effectiveness of using the Moodle-based e-learning platform in improving students’ motivation in the subject of Computer and Basic Networking. The method used was quantitative with a pre-experimental approach and a one-group pretest-posttest design. The research subjects were 33 tenth-grade students at SMKN 2 Kuningan. Data collection techniques were carried out through observation and a learning motivation questionnaire administered before and after the implementation of Moodle. The data were analyzed descriptively and quantitatively. The results showed a significant increase in students’ learning motivation after using Moodle, as evidenced by the Wilcoxon Signed Ranks Test and a large effect size. It is concluded that Moodle is effective in enhancing students’ learning motivation, especially in practice-based and technical subjects. The implication is that Moodle can serve as a strategic alternative for implementing interactive, flexible, and student-centered digital learning, while also encouraging teachers to adopt more innovative, technology-based teaching approache